Human Communication CD-ROM - Judy pearson (Mc Graw Hill, 2003)
Besar file 634 MB, berisi : Animations, Videos, Quizzes for Test Prep, Key Terms Flash Cards with Audio, Business Documents Templates, Outline Tutor 2.0, PowerPoint Tutorial, Learning Assessment tool, Link to Online Learning Center, Judul dalam kemasan.